Analisis Pengaruh Pembentukan Modal Tetap Bruto (PMTB) dan Pembiayaan Bank Syariah Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Natasya Inggriani Powa; Zulgani Zulgani; Ary Dean Amri (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to analyze the effect of Gross Fixed Capital Formation (GFCF) and Islamic bank financing on economic growth in Jambi Province. The data used are secondary data for the period 2010–2024 obtained from the Central Statistics Agency (BPS) and the Financial Services Authority (OJK). The analytical method used is the Autoregressive Distributed Lag (ARDL) model to examine short-term and long-term relationships between variables. The results show that in the short term, GFCF and Islamic bank financing do not have a significant effect on economic growth. However, in the long term, both variables have a significant relationship with economic growth in Jambi Province. This indicates that investment and Islamic financing play an important role in supporting sustainable regional economic growth.